Autism and entrepreneurship: An examination of the effectiveness of self-employment as a model to address the economic isolation experienced by individuals with autism spectrum disorder. - Knott, Gregory (2018)
Individuals with Autism Spectrum Disorder (ASD) are more socially isolated and economically disadvantaged than their peers with other developmental disorders and much greater than the general population (Roux, Shattuck, Rust, Rava, Anderson, 2015, p. 16). Specific data related to the numbers of employed individuals with ASD in Canada are difficult to find. Turcotte’s (2014) study on Persons with disabilities and employment from Statistics Canada did not differentiate disabilities when providing employment levels; it did, however, show that individuals with disabilities are often working at levels significantly lower than their peers not living with a disability. In 2011, Canadians with a disability between the ages of 25 and 64 had an employment rate of 49%, as compared to a rate of 79% for the same age grouping of their peers without a disability (Turcotte, 2014, p. 1). Leading ASD organizations place the unemployment rate for people with ASD at above 80% (Autism Speaks Canada, 2016). Recent studies have shown that 58% of young adults with autism have been employed in the past, as compared to 74% of those with an intellectual disability and 90% of those with an emotional disturbance, speech impairment, or learning disability (Roux, et al, 2015, p. 15). This represents a significant portion of the population which is economically disadvantaged from their communities. While the known statistics paint a grim reality for the obtainment of some independence, many individuals and organizations across North America are taking a different path in creating a reprieve from economic and social isolation of people living with ASD: they are creating enterprises and self-employment opportunities for people with ASD. In Newfoundland and Labrador there is no program in place to specifically address self-employment development opportunities for people with ASD. This represents a gap in supports that the client, the Autism Society, Newfoundland and Labrador (ASNL) wishes to fill. To fill this gap, this project will seek to ...